From Hypothyroidism to Coronary Heart Disease: Unraveling the Lipid Profile Link: A Mendelian Randomization Study - Li, Jinjian; Long, Siyu; Liu, Boyuan; Hong, Shubin; Yu, Shuang; Li, Yanbing; Wu, Dide; Xiao, Haipeng (Journal of the Endocrine Society, 2025)
Hypothyroidism's role in coronary heart disease (CHD) and its link with lipid metabolism is debated. Our study aims to clarify the causal relationship between hypothyroidism and CHD, focusing on the potential mediating effects of lipid profiles. To assess the causal effect of hypothyroidism on the development of CHD and examine the mediating role of lipid profiles through Mendelian randomization (MR). We conducted MR tests using genome-wide association study data of 500 000 participants of European ancestry from FinnGen and UK Biobank, respectively. Bidirectional MR tests were utilized to confirm causality, and the results of an inverse variance weighted method served as the main analysis. Weighted median, MR-Egger, and MR-Pleiotropy Residual Sum and Outlier methods were utilized as sensitivity analyses to validate our findings. We found genetically predicted hypothyroidism increased the risk of CHD by 7.8% [odds ratio (OR) = 1.078, 95% confidence interval (CI) 1.026-1.134, = .003]. This liability was also inversely associated with high-density lipoprotein cholesterol (HDL-C) levels (β = -0.013, 95% CI -0.022-0.004, = .005) and apolipoprotein A-I levels (β = -0.014, 95% CI -0.025-0.004, = .008). HDL-C was inversely associated with coronary heart disease (OR 0.734, 95% CI 0.670-0.803, < .001), and apolipoprotein A-I was also inversely associated with coronary heart disease (OR 0.845, 95% CI 0.768-0.931, < .001). Our findings suggested a causal link between hypothyroidism and increased CHD risk, likely mediated through changes in HDL-C and apolipoprotein A-I levels. This highlights the importance of monitoring lipid levels in hypothyroid patients and calls for further research to explore these relationships and their implications for prevention and treatment strategies.